Phosphate linkers with traceable cyclic intermediates for self-immolation detection and monitoring. Issue 2 (10th December 2020) - Procházková, Eliška; Šimon, Petr; Straka, Michal; Filo, Juraj; Májek, Michal; Cigáň, Marek; Baszczyňski, Ondřej
Abstract : A robust method based on NMR traceable cyclic intermediates clearly distinguished self-immolation from other cargo-release processes. Abstract : Self-immolation (SI) is the key principle of ProTide nucleotide prodrugs such as remdesivir, which is currently used to treat COVID-19 patients. Developing novel tailor-made SI systems requires new analytical methods for the detection and monitoring of SI. We developed a robust method for SI analysis using novel phosphate-based SI linkers with NMR traceable cyclic intermediates to distinguish SI from alternative fragmentation pathways and to monitor cargo release in real time.